Disparity in Judges' Decisions in Narcotics Crime Cases - Raehan, Sri; Erwin, Yulias (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
The purpose of this study is to analyze the disparity in judges' decisions in narcotics crime cases at the Praya District Court and to analyze the disparity in narcotics crime cases according to the theory of justice. This research is a normative legal study using a statutory approach, a conceptual approach, and a case approach. Legal materials were analyzed using literature and the internet. The results of the study indicate that disparity in judgments is influenced by several factors, including differences in legal interpretation by judges, the absence of standard sentencing guidelines, and subjectivity in considering aggravating and mitigating circumstances. Aggravating factors include the defendant's prior criminal record. Mitigating factors include the defendant's cooperative attitude during the trial and a promise not to repeat the offense in the future. Disparity in narcotics-related criminal cases, according to the theory of justice, is viewed from the enforcement of the law to achieve the desired legal justice. Different sentences for similar cases can be considered unfair, as they disregard the principle of “proportionality” between the offense and the punishment. From the perspective of justice theory, this disparity contradicts the principles of distributive and retributive justice because it results in unequal treatment of offenders with similar criminal acts.